A State of Art Review on The Design and Applications of Flexible Microstrip Antennas - Jacob Abraham, (AG Volumes, 2022)
The microstrip antenna is a practical, planar, and simple-to-fabricate antenna that has a number of appealing characteristics and features in addition to a number of glaring restrictions. The passive antenna is a vital aspect of any wireless communications network, for both transmit and receive sides. Using the same antenna for both purposes is possible, but it is also possible to use drastically different ones, depending on the application. It is common to find microstrip antennas in communication systems because of its unique characteristics, including their tiny size, light weight, low profile and flexibility, as well as their cheap production cost. Textile materials are often employed to increase the pliability of microstrip antennas, and they are also inexpensive, with the added benefit of having a low specific absorption rate (SAR). A wide range of applications for flexible microstrip antennas, such as GPS tracking, RFID identification and military usage are possible.